Directed Dehydration of Na4Sn2S6 ⋅ 5H2O Generates the New Compound Na4Sn2S6: Crystal Structure and Selected Properties. Issue 10 (27th January 2023) - Benkada, Assma; Hartmann, Felix; Poschmann, Michael; Indris, Sylvio; Lühmann, Henning; Bensch, Wolfgang
Abstract: The new thiostannate Na4 Sn2 S6 was prepared by directed crystal water removal from the hydrate Na4 Sn2 S6 ⋅ 5H2 O at moderate temperatures. While the structure of the hydrate comprises isolated [Sn2 S6 ] 4− anions, that of the anhydrate contains linear chains composed of corner‐sharing SnS4 tetrahedra, a structural motif not known in thiostannate chemistry. This structural rearrangement requires bond‐breakage in the [Sn2 S6 ] 4− anion, movements of the fragments of the opened [Sn2 S6 ] 4− anion and Sn−S−Sn bond formation. Simultaneously, the coordination environment of the Na + cations is significantly altered and the in situ formed NaS5 polyhedra are joined by corner‐ and edge‐sharing to form a six‐membered ring. Time‐dependent in situ X‐ray powder diffraction evidences very fast rehydration into Na4 Sn2 S6 ⋅ 5H2 O during storage in air atmosphere, but recovery of the initial crystallinity requires several days. Impedance spectroscopy demonstrates a mediocre room‐temperature Na + ion conductivity of 0.31 μS cm −1 and an activation energy for ionic transport of E a =0.75 eV. Abstract : Reversible Dehydration . Directed dehydration of Na4 Sn2 S6 ⋅ 5H2 O at moderate temperatures yields the new compound Na4 Sn2 S6, which can be rehydrated to the hydrate by storage in air at ambient conditions. The crystal structure of the anhydrate features linear Sn2 S6 n 4 − chains formed by corner‐sharing SnS4 tetrahedra, between which Na + ions are arranged in fivefold S 2 − coordination and enable moderate ionic conduction properties.